Visual contrast detection cannot be predicted from surrogate measures of retinal ganglion cell number and sampling density in healthy young adults - Denniss, Jonathan; Turpin, Andrew; McKendrick, Allison M. (Association for Research in Vision and Ophthalmology (ARVO), 2014)
To establish whether a clinically exploitable relationship exists between surrogate measures of retinal ganglion cell number and functional sampling density and visual contrast sensitivity in healthy young eyes.